Relocating the Capital City of Indonesia: A Maqāṣid-Based Critical Evaluation - Asmuni, Asmuni; Farida, Ulfa Jamilatul (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This article aims to critically evaluate the relocation of the capital city of Indonesia based on the principles of al-maqāṣid (the objectives of Islamic law), as outlined in the existing legislation. The relocation of a capital city has historical precedence in Islamic tradition, with its primary justification being the fulfillment of the public good (maslahah). Through a normative legal study, this research reveals that the objective of relocating national capital is fundamentally a secondary need (ḥājiyyāt) rather than a primary necessity (ḍarūriyyāt) for the Indonesian populace. This classification indicates that the process of developing new national capital may face significant challenges in the future, as it does not address an essential or urgent need, but rather a secondary one. Consequently, the potential for encountering serious issues during the development and implementation phases of new capital is high, warranting a careful and well-considered approach to avoid future complications.